Expansão urbana e o direito ao desenvolvimento sustentável na cidade de Cajazeiras - PB: uma análise à luz da função social da cidade - Moraes, Éverton Gonçalves (2019)
Taking into account that the full development of the city will occur when its social functions are fulfilled and the consequent guarantee of the well-being of its inhabitants, and this will happen through the Master Plan, which is mandatory for cities with more than twenty thousand inhabitants, elaborated and duly ordered by the dictates of the Federal Constitution and the City Statute (Law No. 10.257 / 2001). In this way, the objective of the research is to analyze the urban expansion of the city of Cajazeiras - PB, between the years 2010 to 2018, confronting it with the constitutional precepts of the social functions of the city. Thus, a quantitative-qualitative research is used, given the attempt to understand the phenomena from the numerical data collected, such as the number of open allotments in the city, and at the same time, phenomena and subjective conjunctures, for example, the reasons that gave rise to the new urban morphology of the city. The method of approach used was the deductive, starting from a major premise, the constitutional principle of the social function of the city, for a lesser premise, the application of this to the Cajazeiras urbanization process, using as technical procedures the bibliographical and to raise a theoretical debate on the historical influence of capital in the formation of urban space, followed by an approach to the social functions of the city, in order to confront these precepts to the concrete case studied. As a result, it was possible to verify that the management of the public police of urban expansion are not meeting the constitutional precepts pointed out, whereas the collected data show that the city follows in a way inverse to the dictates of sustainability, especially with regard to guaranteeing to the citizen access and effective public policies for housing, education, services, work, health, urban planning, leisure, security, preservation of cultural heritage, historical and natural, urban mobility, democratic participation, and others.